ALGORITHMS AND DISINFORMATION: AUTOMATION OF CHECKS IN LATIN AMERICA - Alencar, Marta (2023)
The circulation of fake news on digital platforms is gaining more and more notoriety due to the influence of bots. In this scenario, fact-checking projects such Lupa, Aos Fatos and Chequeado, work with verification automation to combat with greater agility and in a timely manner, the market of false information. To this end, the research applies a methodology with both theoretical and empirical approaches based on a multiple case study, where it analyzes the agencies' automated products, also citing the technology laboratories created by Lupa, Aos Fatos and Chequeado, for the innovation of their services. Therefore, this article addresses the process of automation of journalistic verification, implemented by fact-checking agencies in Latin America.